2018
DOI: 10.3233/cbm-170088
|View full text |Cite
|
Sign up to set email alerts
|

Rule of changes in serum GGT levels and GGT/ALT and AST/ALT ratios in primary hepatic carcinoma patients with different AFP levels

Abstract: For patients with chronic hepatitis B and cirrhosis after hepatitis B, no matter how AFP level is, when liver function report reveals increased GGT, AST/ALT > 1 and GGT/ALT > 1 (that is, AST > ALT and GGT > ALT), even if AFP is negative, we should also be alert to the existence of PHC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 7 publications
2
38
0
1
Order By: Relevance
“…A significant association between serum Linc00152 and GGT as well as serum PTTG3P and GGT was demonstrated in patients with HCC. GGT is an enzyme which can be induced by intrahepatic obstruction or directly synthesized by liver cancer cells in HCC [26]. The diagnostic value of GGT has been deeply studied, and elevated GGT has been demonstrated to predict poor survival for HCC [27].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A significant association between serum Linc00152 and GGT as well as serum PTTG3P and GGT was demonstrated in patients with HCC. GGT is an enzyme which can be induced by intrahepatic obstruction or directly synthesized by liver cancer cells in HCC [26]. The diagnostic value of GGT has been deeply studied, and elevated GGT has been demonstrated to predict poor survival for HCC [27].…”
mentioning
confidence: 99%
“…Clinically, ALT is a useful indicator of liver injury. When liver cells are damaged, ALT will leak out from the injured cells into the blood, resulting in an increased serum ALT level [26]. Thus, it is suggested that serum SPRY4-IT1 may also be induced by liver injury.…”
mentioning
confidence: 99%
“…To investigate the possible toxicology of the nanomedicine, the indexes of blood chemistry including ALT, AST, ALP, ALB, and TP for liver function and BUN for kidney function were examined. There was no obvious change in ALT, AST, BUN, ALP, ALB, and TP between the saline control and BV/PTX@Au@PDA/DOX with laser irradiation groups ( Figure 5 A) confirming the excellent biosafety of prepared nanomedicine in vivo 36. Furthermore, relative to control groups, the BV/PTX@Au@PDA/DOX plus laser group showed tumor necrosis, and no organ injury or inflammatory lesions were found in all major organs by hematoxylin and eosin (H&E) staining ( Figure 5 B).…”
Section: Resultsmentioning
confidence: 79%
“…In addition to polymorphisms, other aspects of liver disease have been associated with tissue injury: Indeed, liver disease is often a reflection of biochemical abnormalities in liver function, which occurs because of repeated injury (Yang et al, 2018). Among the aminotransferases, ALT was the marker most sensitive to liver injury, which confirms the accuracy of the factor in the identification of changes in cellular integrity (Kim et al, 2008).…”
Section: Discussionmentioning
confidence: 83%